CODE SWITCHING IN “HALUSTIK” MOVIE BY NIA DINATA, LUCKY KUSWANDI, AND ANDRI CHUNG - Rina Husnaini Febriyanti; Hanna Sundari (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
Code-switching (CS) nowadays has been used by youth as a daily language among them and reflected in the “Halustik” movie. The aims of the research are to find out the category of CS spoken by the speakers and to explore their communication intentions to switch from one code to another in the movie which depicts urban life among young people. In the movie, the casts speak and communicate in four languages (Indonesian, English, Javanese, and Sundanese). Qualitative research data were collected by identifying the CS utterances from words, phrases, clauses, and sentences spoken by the main casts/characters in the movie. Next, the data were categorized, selected based on the categories of CS, and classified based on communicative intentions. The findings show that intra-sentential CS (60%) was the most used category of CS, followed by tag CS (4%), and inter-sentential CS (36%). Concerning the communicative intentions by the speakers, they alternate the language into another language since they are intended to talking about a certain topic (60%), quoting someone's words (11%), feeling empathy for something (expressing solidarity) (4%), providing interjection (4%), giving repetition for clarification (7%), clarifying the content of speech to the interlocutor (9%), and expressing a group identity (4%).